The strong hardening effect of Re segregation on edge dislocation lines in W - Pascuet, Maria Ines Magdalena; Fernández, J. R.; Castin, Nicolas; Bonny, G. (Elsevier, 2023)
Fil: Pascuet, Maria Ines Magdalena. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina